PENGARUH MEDIA PEMBELAJARAN BERBASIS ADOBE ANIMATE TERHADAP HASIL BELAJAR IPAS MATERI SEPERTI APAKAH BUDAYA DAERAHKU SISWA KELAS V DI SD NEGERI 2 LAMBHEU - Muhammad Fazril; Mislinawati; Nurmasyitah; Rauzah (Universitas Syiah Kuala, 2026)
This research is motivated by the low learning outcomes of students in regional culture and the lack of use of interactive digital learning media in the learning process. This study aims to determine the effect of Adobe Animate-based learning media on the science learning outcomes of fifth-grade students at Lambheu 2 Public Elementary School SD Negeri 2 Lambheu in the subject